Environmental Emissions and Economic Growth: Evidence from Highly Polluting Countries - Aziz Ullah,; Dr. Mirajul Haq,; Dr. Malik Muhammad, (Al-Qanṭara, 2024)
The studies in the field of energy and environmental economics focus on examining the determinants of environmental emissions namely , or ecological footprint while analyzing the environmental emissions economic growth relationship. This study examines the impact of green growth and other determinants on four types of environmental emissions. The study is carried out for a sample of highly polluted countries over the period 1990 to 2018. The second-generation panel data methods such as Pesaran (2007) test for cross-section dependence, Pesaran and Yamagata (2008) test for slopes homogeneity/heterogeneity, Bai and Carrion (2009) unit root test, Westerlund & Edgerton's (2008) co-integration-test, and cross-sectional augmented Auto-regressive distributive lag model are used for dynamic analysis. Results reveal that there is a stable long-run relationship between variables of interest. The financial development is found to increase emissions. Moreover, higher per capita GDP growth deteriorates the environment. The results model also suggests that an increase in environment-related taxes, non-renewable energy, and per capita GDP increases emissions. Similarly, results indicate that per capita consumption of ecological footprint increases with the increase of green growth and non-renewable energy.